Protocol for the Houston Hospital-based violence intervention program. - Alexander Testa; Eresha Bluth; Latanya Monroe; Karlton Harris; Sarah Beth Abbott; Mary E Aitken; Erin E Fox; Brian Heckler; Lillian S Kao; Ruosha Li; Susannah Meg Michael; Heidi M McPherson; et al. (PLoS ONE)
Firearm violence is a leading cause of injury and mortality in the United States. Hospital-based violence intervention programs (HVIPs) are a promising public health strategy designed to reduce recurrent violence by engaging patients during hospitalization and connecting them to support services after discharge. This protocol describes the design and implementation of the Houston Hospital-Based Violence Intervention Program (Houston-HVIP), which will be evaluated by a randomized controlled trial conducted at a Level 1 trauma center in Houston, Texas. The study plans to enroll individuals aged 16-35 who present with gunshot wounds (GSW) at the Level 1 trauma center. Participants are randomized to either a treatment group receiving six months of intensive case management with direct referrals to social services or a control group receiving usual care, which involves indirect referral and limited case management. The primary outcome is a composite measure of an individual's exposure to firearm violence via (a) self-report, (b) hospital admission records, and (c) mortality records. Secondary outcomes measured at the individual level assess violent reinjury, attitudes toward violence, post-traumatic stress, aggression, and self-rated health. Outcomes are assessed at baseline and 3-, 6-, 9-, and 12-months post-enrollment. The study will enroll 274 participants and include both quantitative and qualitative assessments to evaluate program impact and participant experience. This protocol aims to contribute to the design and implementation of HVIPs in large Level 1 trauma centers.